Una comparación empírica de algunos métodos de inicialización EM y criterios de selección de modelos para mezclas de distribuciones normales asimetricas - Pereira, José R.; Marques, Leyne A.; da Costa, José M. (Revista Colombiana de Estadística, 2012)
We investigate, via simulation study, the performance of the EM algorithm for maximum likelihood estimation in finite mixtures of skew-normal distributions with component specific parameters. The study takes into account the initialization method, the number of iterations needed to attain a fixed stopping rule and the ability of some classical model choice criteria to estimate the correct number of mixture components. The results show that the algorithm produces quite reasonable estimates when using the method of moments to obtain the starting points and that, combining them with the AIC, BIC, ICL or EDC criteria, represents a good alternative to estimate the number of components of the mixture. Exceptions occur in the estimation of the skewness parameters, notably when the sample size is relatively small, and in some classical problematic cases, as when the mixture components are poorly separated.